JĘZYKI I PAMIĘĆ KULTUROWA. O GLOTTODYDAKTYCZNYM POTENCJALE MIEJSC PAMIĘCI - Badstübner-Kizik, Camilla (Neofilolog, 2019)
Looking for motivating concepts to stimulate integrated language and culture-related teaching and learning processes in the foreign language classroom, the vibrant concept of Cultural Memory is certainly an issue to pay attention to. It offers a variety of occasions for language and culture awareness training tightly connected with language learning, reaching far beyond traditional regional studies. Realms of memory, acting as products and markers of a complex cultural memory, can reveal to what extent (by whom, by which means, to what aims) cultural patterns and meanings are constructed, how they change or under which circumstances they survive long periods of time. Up-to-date foreign language didactics can make use of this in aiming at symbolic competence (Claire Kramsch). Understanding culture as an ongoing process of (de-and re- )construction, learners might be enabled to notice and (partly) participate in authentic discourses, going on in different languages. Realms of memory, manifesting themselves per definition e.g. as texts, pictures, sounds, buildings, historic or mythic persons, objects, terms or whole cultural concepts, own a considerable linguistic and cultural potential. This clearly points at content and process oriented learning processes involving the foreign language as a natural means of exploration. The article discusses criteria which might help to choose realms of memory suitable for the foreign language classroom and takes a look at two genuinely “German-speaking” examples in the field of sport (Córdoba 1978) and everyday objects (Schweizermesser). They can illustrate the wide range of didactic possibilities and stimulating methods which arise from authentic and vivid parts of a widely understood culture.